Analysis of the Influence of Life Expectancy, Average Years of Schooling, and Gross Regional Domestic Product (GDP), on the Human Development Index in Denpasar City. - Remario, Juan; Wijaya, Riko Setya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the impact of life expectancy, average years of schooling, and Gross Regional Domestic Product (GRDP) on the Human Development Index (HDI) in Denpasar City. Utilizing annual data from 2010 to 2021 sourced from the Central Statistics Agency (BPS), the study employs multiple linear regression analysis to discern the relationships among these variables. The findings indicate that both life expectancy and average years of schooling have a positive and significant effect on the HDI in Denpasar City. In contrast, GRDP exhibits a positive but insignificant effect on HDI. These results suggest that enhancing the quality of health and education is the primary driver for improving HDI in Denpasar City. Consequently, initiatives aimed at improving community welfare in Denpasar should prioritize advancements in health and education to achieve superior human development outcomes.